Cognitive rehabilitation using occupational therapy models for adults with cognitive impairment: a case series - Pai, Anuradha V.; Bankhele, Jyotsna R. (International Journal of Advances in Medicine, 2020)
Occupational Therapy is one of the primary professions with knowledge and skills to address the consequences of cognitive decline. Cognitive decline is caused by traumatic brain injury, non-traumatic neurological diseases, Ageing, Chronic psychiatry diseases. Recent thinking on cognitive rehabilitation places various approaches to a continuum, from restorative/ remedial approaches to cognitive compensatory approaches with four models within OT, and functional environmental approach with three models of intervention. Before using any of the above models, it is necessary to assess the needs of the patient, the demands of the environment and his cognitive ability. The issues faced by persons with cognitive dysfunctions demand interdisciplinary work to link the brain, behaviour and performance in everyday life. A 36-year-old male, 4years post-traumatic brain injury with anosognosia, disorientation and anomia was treated using a dynamic interactional model of cognitive retraining and showed dramatic recovery after 8 weeks’ therapy. A 65-year-old female diagnosed as Alzheimer's Dementia since two years with memory problems, neglect of ADL and visual hallucinations, disinhibited behaviour was treated for 8 weeks using Cognitive Disabilities model of 2011 and showed moderate recovery. A 73-year-old male diagnosed as Alzheimer's Dementia with forgetfulness, difficulty in money handling, disorientation and dependent in ADL was treated using Cognitive Disability Reconsidered model showed slight recovery. Each individual with cognitive problems due to disease, trauma and ageing behaves separately. Occupational therapy aims at maintaining independence in ADL and achieving the maximum level of performance in work and leisure.